In vitro enantioselective pharmacodynamics of Carprofen and Flunixin‐meglumine in feedlot cattle. Issue 1 (25th April 2013) - Miciletta, M.; Cuniberti, B.; Barbero, R.; Re, G.
<x xml:space="preserve">Abstract</x> The activity of the anti‐inflammatory agents Flunixin‐meglumine (FLU), RS (±) Carprofen (CPF) and S (+) CPF on bovine cyclooxygenases (COXs) has been characterized in feedlot calves using an in vitro whole blood model. The drugs showed equivalent efficacy in their inhibitory activity on COXs, and the rank order of potency for both COX‐1 and COX‐2 inhibition was FLU > S (+) CPF > RS (±) CPF. Our results indicated that FLU is a nonselective inhibitor of bovine COXs, whereas RS (±) CPF and S (+) CPF exhibited different degrees of preferential inhibition of COX‐2 isoenzyme. The rank order of IC50 COX‐1: IC50 COX‐2 potency ratios was in fact S (+) CPF (51.882) > RS (±) CPF (13.964) > FLU (0.606), and the calculated percentage inhibition of COX‐1 corresponding to COX‐2 inhibition values comprised between 80% and 95% was comprised between 57.697 and 79.865 for FLU, 33.373 and 51.319 for RS (±) CPF, and 0.230 and 4.622 for S (+) CPF, respectively. These findings are discussed in relation to the prediction of the clinical relevance of COX inhibition by the test drugs in cattle.